MENINGKATKAN MUTU PENDIDIKAN ISLAM - Munzir Munzir (Universitas Negeri Medan, 2022)
Improving the Quality of Islamic Education. This article aims to explain improving the quality of Islamic education which includes; the quality of Islamic education and efforts to improve the quality of Islamic education. The quality of Islamic education is the ability of a school or madrasa educational institution to manage operationally and efficiently the components related to the school or madrasa so that the quality of inputs, processes, outputs, and school outcomes is guaranteed so that the madrasa or school can generate added value to the community. components according to norms or standards that are currently in force in schools and madrasa in achieving results from tests of academic ability or non-academic achievement. Meanwhile, efforts to improve the quality of Islamic education are through the management of improving the quality of Islamic education, improving the quality of Islamic education, namely through improving the quality of educators, improving the quality of learning and improving madrasa relations. with the people and society at large.